2004
DOI: 10.1590/s0103-84782004000200027
|View full text |Cite
|
Sign up to set email alerts
|

Uso de enzimas em dietas contendo níveis crescentes de farelo de arroz integral para frangos de corte

Abstract: O experimento foi realizado com o objetivo de determinar o desempenho e o rendimento de carcaça de frangos de corte alimentados com dietas contendo níveis crescentes de farelo de arroz integral (FAI), suplementadas ou não com enzimas. Foram utilizados 960 pintos de corte, machos e fêmeas da linhagem Cobb distribuídos em um delineamento experimental inteiramente casualizado, com oito tratamentos e seis repetições de 20 aves. Utilizaram-se 4 níveis de FAI (0%, 10%, 20% e 30%), com e sem suplementação de um compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 5 publications
2
1
0
7
Order By: Relevance
“…Feed intake was the least in birds fed rice bran, broken rice and in fasting birds, noting that the latter started to receive feed ad libitum on the 10th experimental day. This agrees with Bonato et al (2004), who, studying feeds with increasing levels of rice bran, observed the occurrence of a decrease in feed intake when birds were fed levels of rice bran addition above 30%. Similar results were found by Santos et al (2004), who observed that as level of inclusion of rice bran in the diet was increased, the feed intake and body weight of birds decreased.…”
Section: Resultssupporting
confidence: 91%
“…Feed intake was the least in birds fed rice bran, broken rice and in fasting birds, noting that the latter started to receive feed ad libitum on the 10th experimental day. This agrees with Bonato et al (2004), who, studying feeds with increasing levels of rice bran, observed the occurrence of a decrease in feed intake when birds were fed levels of rice bran addition above 30%. Similar results were found by Santos et al (2004), who observed that as level of inclusion of rice bran in the diet was increased, the feed intake and body weight of birds decreased.…”
Section: Resultssupporting
confidence: 91%
“…The nutritional reduction of the diets was not offset by the effect of the enzyme complexes under study. This result corroborates other authors who reported effects of diet density on broiler performance despite enzyme supplementation (Bonato et al 2004). In practical terms, this result demonstrates that for the products tested here to be used without performance losses, these levels should be reduced to no more than 100 Kcal ME/kg apparent ME, 3% limiting AA, and 2 units of crude protein.…”
Section: Factorsupporting
confidence: 93%
“…Pelos resultados obtidos, observou-se que houve diferença significativa (P<0,01) entre os tratamentos para ganho de peso e conversão alimentar, sem haver, portanto, interferência da utilização da fitase sobre as duas rações sugeridas pelas empresas. Estes resultados coincidem com os obtidos por Bonato et al (2001), McKnight (1999 e Sebastian et al (1996).…”
Section: Período De Crescimento (22 a 35 Dias De Idade)unclassified